A qualitative stress analysis of a cross section of the trabecular bone tissue of the femoral head by photoelasticity - Rodríguez Lelis, J. M.; Vargas Treviño, Marciano; Navarro Torres, J.; Abundez P., Arturo; Reyes Galindo, Sergio; Vela Arvizo, Dagoberto (Revista Mexicana de Ingenieria Biomedica, 2007)
In this work, a qualitative analysis of the stress distribution of the femoral head of a human femur by photoelasticity is presented. A model of the cross section was obtained by plaster casting, carefully maintaining the internal architecture of the porous bone. Here punctual loading was applied aimed to evaluate the trabecular behavior. The fringe patterns observed in the porous bone model showed that the maximum stress concentration is shifted from the surface to the interior of the bone, allowing the damping of external forces and diffused them towards the interior of the bone tissue, thus reducing the contact stresses at the surface of the femoral head joint. These results showed that solid models will tend to mislead the stress behavior within the bone.